Cows, Cliffs, and Caves: Exploring the Angloseen of James Ward’s Gordale Scar - Mesplède, Sophie (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2025)
This paper revisits Gordale Scar, a painting created in 1812–1814 by the English artist James Ward (1759–1869), in the light of the ecocritical concept of the Angloseen recently developed by Charlotte Gould and Sophie Mesplède to better apprehend the environmental implicit of the changing landscapes of the Anglocene. It intends to bring out the contemporary technological, social, and animal histories that make up the unseen of a monumental composition intended to impress through its sublime aesthetics and thus celebrate a wild and immemorial landscape.